2006
DOI: 10.1127/0029-5035/2006/0083-0511
|View full text |Cite
|
Sign up to set email alerts
|

Four rhytismataceous ascomycetes on needles of pine from China

Abstract: Three species of Rhytismataceae are described from needles of pines from China. Davisomycella intermedia is a new species growing on Pinus yunnanensis var. tenuifolia. Ploioderma pini-armandii and Soleella pinicola on Pinus armandii have been described previously only in Chinese with a short Latin diagnosis and therefore are presented here in detail. Naemacyclus fimbriatus, formerly regarded as belonging to the Rhytismatales, now to Helotiales, is reported for the first time for China, described, and illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Accumulating studies show that some fungal taxa appear with high frequency in Pinaceae, but are usually absent from other plant lineages. Lophodermium, Pezicula, and Phialocephala are often the dominant conifer endophytes (Bills 1996;M€ uller et al 2001;Hou et al 2006;Arnold 2007;Sieber 2007). In our study, the dominant and rare taxa belonging to Rhytismataceae and Helotiales were identified.…”
Section: The Biodiversityefunctional Relationship In Saprophytic and mentioning
confidence: 97%
“…Accumulating studies show that some fungal taxa appear with high frequency in Pinaceae, but are usually absent from other plant lineages. Lophodermium, Pezicula, and Phialocephala are often the dominant conifer endophytes (Bills 1996;M€ uller et al 2001;Hou et al 2006;Arnold 2007;Sieber 2007). In our study, the dominant and rare taxa belonging to Rhytismataceae and Helotiales were identified.…”
Section: The Biodiversityefunctional Relationship In Saprophytic and mentioning
confidence: 97%
“…After Minter's study, many new taxa of Lophodermium on needles of Pinus spp. have been proposed (He et al 1986;Lin and Tang 1988;Hou and Liu 1990;Liu and Qiu 1995;Hou et al 1996;Lin et al 1993, 1995a, b, Sokolski et al 2004Hou and Piepenbring 2006). In the present paper, we describe a further species of Lophodermium on Pinus mugo Turra from Oberstdorf in the German Alps based on morphological and molecular data.…”
Section: Introductionmentioning
confidence: 68%
“…As chemical reagents or investigation media, distilled water, Meltzer's reagent and Congo red were used. Identification of the samples were perfored by comparing the obtained data with DiCosmo et al (1983), Breitenbach and Kränzlin (1984), Wang (2005), Hou et al (2006), Zhang et al (2009), Medel et al (2013), Guo et al 2014, Ivanová (2015) and Quijada et al (2015). Dried fruit bodies are kept at Karamanoğlu Mehmetbey University, Kamil Özdağ Science Faculty, Department of Biology.…”
Section: Methodsmentioning
confidence: 99%